Electrochemical-corrosion-resistant Ti-6Al-4V alloy pulsed by direct current and preparation method of electrochemical-corrosion-resistant Ti-6Al-4V alloy
The treatment of Ti-6Al-4V alloy through DC pulse technology solves its electrochemical corrosion problem in the human body fluid environment, significantly improving its electrochemical corrosion performance and biosafety.
Patent Information
- Application Number
- CN202411757264.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Ti-6Al-4V titanium alloy still faces electrochemical corrosion problems in human body fluid environment, causing the spread of corrosion products and causing physical harm.
The Ti-6Al-4V alloy is processed by direct current pulse technology. Through instantaneous high current density DC pulses, grain boundary vanadium diffusion is induced, dislocation is released, and electrochemical corrosion is reduced.
The electrochemical corrosion performance of Ti-6Al-4V alloy in NaCl electrolyte environment has been significantly improved, forming a denser passivation film, reducing corrosion rate and improving biosafety.
Smart Images

Figure CN119615033A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of titanium alloy corrosion resistance, and in particular relates to a Ti-6Al-4V alloy resistant to electrochemical corrosion using direct current pulses and a preparation method thereof. Background Art
[0002] Ti-6Al-4V (TC4) dual-phase titanium alloy has been widely used in biomedicine due to its superior mechanical properties, stable physical and chemical properties, excellent biocompatibility, good corrosion resistance and other advantages. It is often used as a biorepair material in the fields of dental implants, vascular stents and artificial orthopedic joints. - 、Na + PO3 3- Electrolytes and organic substances such as proteins and phospholipids, titanium alloys still inevitably face problems such as ion precipitation, local corrosion, and wear, which leads to the diffusion of corrosion products into the human tissues around the implant, causing a series of problems such as physiological hazards. Therefore, further optimizing and improving the corrosion resistance of Ti-6Al-4V titanium alloy and optimizing the biosafety of titanium alloys have clear and far-reaching practical significance. At present, researchers have carried out a series of surface treatment technologies to optimize the electrochemical properties of titanium alloys in a targeted manner. For example, patent CN103233260 A proposes to prepare an anti-fouling and anti-damage ceramic film on the surface of Ti-6Al-4V alloy by a micro-arc oxidation technology. Compared with the titanium alloy matrix, this technology significantly optimizes the electrochemical corrosion performance, hardness and wear resistance. Patent CN201010173044.6 obtains a cast titanium alloy with significantly improved mechanical properties, corrosion resistance and wear resistance by solid solution treatment of indium elements into the titanium matrix, which is suitable for the design and production of high-precision and small-volume implants.
[0003] At present, direct current pulse assisted forming or deformation technology has achieved microstructure regulation and mechanical property optimization of various metal material systems. Direct current pulse technology usually has the advantages of simple equipment operation, short preparation cycle, and low production energy consumption. It can usually significantly optimize the comprehensive mechanical properties of titanium alloys in a short time. At present, the changing rules of electrochemical corrosion performance regulated by electric pulse technology are still unclear. Summary of the invention
[0004] In order to solve the practical problems that the electrochemical corrosion performance of Ti-6Al-4V alloy materials in the background technology still needs to be further improved and the risk of harm caused by corrosion products is relatively high, the main purpose of the present invention is to provide an electrochemical corrosion-resistant Ti-6Al-4V alloy using a direct current pulse and a preparation method thereof, so as to instantly and efficiently achieve significant optimization of the electrochemical corrosion performance of the Ti-6Al-4V alloy in a NaCl electrolyte environment.
[0005] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows, comprising the following steps:
[0006] Step S1, first, wire cutting is performed on the Ti-6Al-4V alloy raw material to obtain a plurality of electrochemical corrosion samples; wherein the Ti-6Al-4V alloy raw material adopts a commercial hot-processed Ti-6Al-4V alloy round rod, and the geometric dimensions of the Ti-6Al-4V alloy round rod are 30 mm in diameter and 200 mm in length. Subsequently, wire cutting is performed along the axial length direction of the alloy round rod to obtain a plurality of electrochemical corrosion samples. The dimensions of the electrochemical corrosion samples are 13 mm in length, 4 mm in width, and 1.5 mm in thickness;
[0007] Step S2, mechanically grinding, ultrasonically cleaning and constant temperature drying the electrochemically corroded sample obtained in step S1 in sequence to obtain an initial alloy sample for direct current pulse treatment;
[0008] Step S3, then placing the initial alloy sample of step S2 on the test bench, and connecting two ends of the initial alloy sample to two copper plate electrodes in the power supply system respectively;
[0009] The power source adopts ISB-300A inverter welding power source, and the current density and direct current pulse processing time are controlled by an external numerical control panel on the power source.
[0010] Step S4, starting the power supply, subjecting the initial alloy sample to direct current pulse treatment, and subjecting the initial alloy sample after direct current pulse treatment to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence, and finally obtaining an electrochemical corrosion resistant Ti-6Al-4V alloy.
[0011] Step S5, all electrochemical tests are performed by a standard three-electrode system, and an electrolyte with a concentration of 0.9wt.% NaCl is added to the electrolytic cell of the standard three-electrode system until the electrolyte liquid level is tangent to the lower surface of the platinum electrode clamp, ensuring that the electrochemical corrosion-resistant Ti-6Al-4V alloy sample to be tested is completely immersed in the electrolyte; the installed electrolytic cell is placed on a constant temperature stage to ensure that the temperature of the electrolyte is 37°C during the entire test process; after the test is completed, the average values of the electrochemical impedance, corrosion current and corrosion potential of the alloy sample are obtained to ensure the reliability of the data.
[0012] In the step S3, a conductive copper block is arranged between the copper plate electrode and the end of the initial alloy sample, and the conductive copper block is used to conduct electricity to the initial alloy sample.
[0013] In step S4, the specific method of performing direct current pulse treatment on the initial alloy sample is: starting the power supply and inputting an instantaneous direct current pulse of a specific current density into the initial alloy sample.
[0014] In step S4, the current density of the instantaneous DC pulse is 130A / mm 2 ~150A / mm 2 .
[0015] In the step S4, the DC pulse processing time of the instantaneous DC pulse is 35 ms to 80 ms.
[0016] In step S4, the current density of the instantaneous DC pulse is 140A / mm 2 , the DC pulse processing time of the instantaneous DC pulse is 70ms.
[0017] In step S4, the application rate of the instantaneous direct current pulse is greater than 11.4 K / ms.
[0018] An induction coil device is installed at the input cable of the power supply, and the induction coil device is used to measure the current value released instantaneously by the power supply, and ensure that the error range between the actual current value tested by the induction coil device and the target current value is ±5A; a thermistor-type infrared thermometer is arranged at the center position of the initial alloy sample, and the thermistor-type infrared thermometer is used to measure the temperature rise of the initial alloy sample during the direct current pulse treatment process.
[0019] In the step S1, the chemical composition of the Ti-6Al-4V alloy raw material mainly includes: Ti, Al, V, Fe, C, and N; the mass percentage content of the aluminum Al element is 5.5% to 6.8%, the mass percentage content of the vanadium V element is 3.5% to 4.5%, the mass percentage content of the iron Fe element is 0.3% to 0.4%, the mass percentage content of the carbon C element is 0.1% to 0.2%, and the mass percentage content of the nitrogen N element is 0.05% to 0.1%.
[0020] The electrochemical corrosion resistant Ti-6Al-4V alloy of the present invention is prepared by adopting the above preparation method.
[0021] The present invention uses instantaneous direct current pulses, and the principle is significantly different from that of electric pulses with long power-on periods. The present invention uses a short millisecond pulse to quickly heat at a rate of at least 11.4K / ms, so that the electric pulse is linearly heated from room temperature 25°C to 882°C within 75ms. The instantaneous increase in energy triggers the rearrangement of atoms inside the material, inducing the diffusion of vanadium at the grain boundary into the crystal, and the movement of dislocations inside the material can release and regulate the residual compressive stress in the crystal, which inhibits the occurrence of local pitting during electrochemical corrosion. In addition, after being treated with electric pulses, the passivation film on the surface of the sample is denser and thicker, effectively blocking the contact between the electrolyte and the Ti substrate and reducing the corrosion rate. The increase in open circuit potential / corrosion potential / charge transfer resistance makes the voltage required for the Ti alloy substrate to undergo Cl- ion corrosion in the electrolyte higher, significantly improving the electrochemical corrosion performance.
[0022] Under the premise of ensuring a stable current density, the present invention accurately obtains the optimal duration of the power-on treatment by adjusting the power-on time of the titanium alloy sample. For example, if a fixed current density of 140A / mm is selected 2 When the electric pulse is used for treatment for different durations of 65ms and 70ms, the electrochemical test samples prepared by the above two sets of electric pulse parameters are subjected to repetitive electrochemical corrosion tests.
[0023] The present invention intends to use direct current pulse equipment to perform electric pulse treatment on the electrochemical corrosion samples of hot-processed Ti-6Al-4V alloy cuboids, explore different electric pulse durations, and achieve efficient and short-process preparation of excellent electrochemical corrosion-resistant Ti-6Al-4V alloy without complex processes such as thermal-mechanical treatment. Therefore, by applying direct current pulse treatment technology to optimize the electrochemical properties of commercial hot-processed Ti-6Al-4V alloy, the alloy preparation cycle and energy consumption are significantly shortened, which has strong practical significance and application prospects. By constructing a simulated human body fluid environment of 37°C and 0.9wt.% NaCl electrolyte and selecting appropriate direct current pulse treatment parameters, the electrochemical corrosion performance of titanium alloy is significantly improved, which can effectively avoid problems such as physiological hazards caused by corrosion products.
[0024] The beneficial effects of the present invention are:
[0025] 1. The present invention performs direct current pulse treatment on commercial hot-processed Ti-6Al-4V alloy, constructs an electrolyte environment, and can effectively improve the electrochemical corrosion resistance of Ti-6Al-4V electrochemical corrosion samples.
[0026] 2. Through the efficient direct current pulse processing method provided by the present invention, the power-on cycle is extremely short at the level of several microseconds, and the operation is simple and convenient. The direct current pulse makes the passivation film formed on the surface of the electric pulse Ti-6Al-4V alloy sample have more ideal electrochemical corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Comparative Example 1, Example 1-2 is a curve showing the change of open circuit potential of Ti-6Al-4V alloy in 0.9wt.% NaCl electrolyte at 37°C over time;
[0028] Figure 2 Comparative Example 1, Tafel polarization curve of Example 1-2Ti-6Al-4V alloy in 0.9wt.% NaCl electrolyte at 37°C;
[0029] Figure 3 This is the electrochemical impedance spectrum of Comparative Example 1, Example 1-2Ti-6Al-4V alloy in 37°C, 0.9wt.% NaCl electrolyte. DETAILED DESCRIPTION
[0030] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] Commercial hot-processed Ti-6Al-4V alloy was selected as the initial material for the electrochemical corrosion performance test. It was first subjected to direct current pulse treatment, and then its electrochemical corrosion performance was analyzed in detail:
[0033] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with dimensions of 30 mm in diameter and 200 mm in length were wire cut to obtain multiple groups of rectangular electrochemical samples with length, width and thickness of 13 mm, 4 mm and 1.5 mm respectively;
[0034] (2) The rectangular electrochemical sample obtained in step (1) is subjected to mechanical grinding with sandpaper to 2000#, ultrasonic cleaning and constant temperature drying in sequence to obtain an initial state sample for electrochemical testing.
[0035] (3) Using a direct current pulse device for processing, the initial state sample is placed on a sample fixture external to the inverter welding power supply device;
[0036] (4) A conductive copper block is placed at the gap between the electrochemical sample and the copper plate electrode and fixed with fastening bolts to ensure a close fit between the three.
[0037] (5) After the electrochemical sample is installed, set the input current of the inverter welding power supply to 840A to ensure that the average current density passing through the cross section of the electrochemical sample is 140A / mm 2 ;
[0038] (6) Set the duration of the electric pulse treatment to 65 ms (hereinafter referred to as 140 A / mm 2 -65ms sample), turn on the DC power supply. After the DC pulse treatment is completed, when the specimen is completely cooled to room temperature, remove the sample from the fixture;
[0039] (7) An induction coil device was installed on the outside of the input cable of the power supply, and the current value released instantly by the power supply was measured to ensure that the test current value of the induction coil was within the range of 835 to 845 A.
[0040] (8) Mechanical grinding with sandpaper to 2000#, ultrasonic cleaning and constant temperature drying were performed in sequence to remove the surface oxide layer and impurities of the electrochemical sample to obtain an electrochemical corrosion-resistant Ti-6Al-4V alloy, completing the sample preparation for electrochemical testing;
[0041] (9) All electrochemical tests were performed using a standard three-electrode system powered by a Princeton 3000A-DX electrochemical workstation. 2 The platinum electrode was used as the counter electrode and the saturated calomel electrode (SCE) was used as the reference electrode. The defect-free initial state sample was loaded on the platinum electrode holder to expose a 10×4mm 2 As working electrode;
[0042] (10) Assemble the three electrodes in a C001 sealed electrolytic cell, and add an electrolyte with a concentration of 0.9 wt.% NaCl into the electrolytic cell using a dropper until the electrolyte surface is tangent to the lower surface of the platinum electrode clamp, ensuring that the test sample is completely immersed in the electrolyte;
[0043] (11) Place the installed electrolytic cell on a constant temperature stage to ensure that the temperature of the electrolyte remains at 37°C during the entire test process;
[0044] (12) First, an open circuit potential test was performed. The open circuit potential was read from the moment the working electrode was placed in the electrolyte and recorded continuously for 40,000 seconds. After the test potential stabilized, the open circuit potential value was read.
[0045] (13) Then, at an open circuit potential of 0.1 to 10 5In the frequency range of Hz, the electrochemical impedance spectrum was collected with an AC signal of 10 mV as the amplitude, and the measurement results were read using Versa.Studio v2.66.2 software;
[0046] (14) Under open circuit potential, the initial potential of the Tafel polarization curve test was set to -0.25 V vs OC, the termination potential was set to 0.25 V vs OC, and the scan rate was set to 0.1666 mV / s;
[0047] (15) The above tests were repeated and the average values of open circuit potential, electrochemical impedance, corrosion current and corrosion potential were read and calculated to ensure the reliability of the data.
[0048] Example 2
[0049] Commercial hot-processed Ti-6Al-4V alloy was selected as the initial material for the electrochemical corrosion performance test. It was first subjected to direct current pulse treatment, and then its electrochemical corrosion performance was analyzed in detail:
[0050] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with dimensions of 30 mm in diameter and 200 mm in length were wire cut to obtain multiple groups of rectangular electrochemical samples with length, width and thickness of 13 mm, 4 mm and 1.5 mm respectively;
[0051] (2) The rectangular electrochemical sample obtained in step (1) is subjected to mechanical grinding with sandpaper to 2000#, ultrasonic cleaning and constant temperature drying in sequence to obtain an initial state sample for electrochemical testing.
[0052] (3) Using a direct current pulse device for processing, the initial state sample is placed on a sample fixture external to the inverter welding power supply device;
[0053] (4) A conductive copper block is placed at the gap between the electrochemical sample and the copper plate electrode and fixed with fastening bolts to ensure a close fit between the three.
[0054] (5) After the electrochemical sample is installed, set the input current of the inverter welding power supply to 840A to ensure that the average current density passing through the cross section of the electrochemical sample is 140A / mm 2 ;
[0055] (6) Set the duration of the electric pulse treatment to 70 ms (hereinafter referred to as 140 A / mm 2 -70ms sample), turn on the DC power supply. After the DC pulse treatment is completed, when the specimen is completely cooled to room temperature, remove the sample from the fixture;
[0056] (7) An induction coil device was installed on the outside of the input cable of the power supply, and the current value released instantly by the power supply was measured to ensure that the test current value of the induction coil was within the range of 835 to 845 A.
[0057] (8) Mechanical grinding with sandpaper to 2000#, ultrasonic cleaning and constant temperature drying were performed in sequence to remove the surface oxide layer and impurities of the electrochemical sample to obtain an electrochemical corrosion-resistant Ti-6Al-4V alloy, completing the sample preparation for electrochemical testing;
[0058] (9) All electrochemical tests were performed using a standard three-electrode system powered by a Princeton 3000A-DX electrochemical workstation. 2 The platinum electrode was used as the counter electrode and the saturated calomel electrode (SCE) was used as the reference electrode. The defect-free initial state sample was loaded on the platinum electrode holder to expose a 10×4mm 2 As working electrode;
[0059] (10) Assemble the three electrodes in a C001 sealed electrolytic cell, and add an electrolyte with a concentration of 0.9 wt.% NaCl into the electrolytic cell using a dropper until the electrolyte surface is tangent to the lower surface of the platinum electrode clamp, ensuring that the test sample is completely immersed in the electrolyte;
[0060] (11) Place the installed electrolytic cell on a constant temperature stage to ensure that the temperature of the electrolyte remains at 37°C during the entire test process;
[0061] (12) First, an open circuit potential test was performed. The open circuit potential was read from the moment the working electrode was placed in the electrolyte and recorded continuously for 40,000 seconds. After the test potential stabilized, the open circuit potential value was read.
[0062] (13) Then, at an open circuit potential of 0.1 to 10 5 In the frequency range of Hz, the electrochemical impedance spectrum was collected with an AC signal of 10 mV as the amplitude, and the measurement results were read using Versa.Studio v2.66.2 software;
[0063] (14) Under open circuit potential, the initial potential of the Tafel polarization curve test was set to -0.25 V vs OC, the termination potential was set to 0.25 V vs OC, and the scan rate was set to 0.1666 mV / s;
[0064] (15) The above tests were repeated and the average values of open circuit potential, electrochemical impedance, corrosion current and corrosion potential were read and calculated to ensure the reliability of the data.
[0065] Comparative Example 1
[0066] Commercial hot-processed Ti-6Al-4V alloy was selected as the initial material for the electrochemical corrosion performance test, and its electrochemical corrosion performance was analyzed in detail:
[0067] (1) First, commercial hot-processed Ti-6Al-4V alloy round bars with dimensions of 30 mm in diameter and 200 mm in length were wire cut to obtain multiple groups of rectangular samples with length, width and thickness of 13 mm, 4 mm and 1.5 mm respectively;
[0068] (2) The rectangular parallelepiped sample obtained in step (1) is subjected to mechanical grinding with sandpaper to 2000#, ultrasonic cleaning and constant temperature drying in sequence to obtain an initial state sample for electrochemical testing. The initial state sample is set as the reference group and is not subjected to any direct current pulse treatment;
[0069] (3) All electrochemical tests were performed using a standard three-electrode system powered by a Princeton 3000A-DX electrochemical workstation. 2 The platinum electrode was used as the counter electrode and the saturated calomel electrode (SCE) was used as the reference electrode. The defect-free initial state sample was loaded on the platinum electrode holder to expose a 10×4mm 2 As working electrode;
[0070] (4) Assemble the three electrodes in a C001 sealed electrolytic cell, and use a dropper to add an electrolyte with a concentration of 0.9 wt.% NaCl into the electrolytic cell until the electrolyte surface is tangent to the lower surface of the platinum electrode clamp, ensuring that the test sample is completely immersed in the electrolyte;
[0071] (5) Place the installed electrolytic cell on a constant temperature stage to ensure that the temperature of the electrolyte remains at 37°C during the entire test process;
[0072] (6) First, an open circuit potential test was performed. The open circuit potential was read from the moment the working electrode was placed in the electrolyte and recorded continuously for 40,000 seconds. After the test potential stabilized, the open circuit potential value was read.
[0073] (7) Then, at an open circuit potential of 0.1 to 10 5 In the frequency range of Hz, the electrochemical impedance spectrum was collected with an AC signal of 10 mV as the amplitude, and the measurement results were read using Versa.Studio v2.66.2 software;
[0074] (8) Under open circuit potential, the initial potential of the Tafel polarization curve test was set to -0.25 V vs OC, the termination potential was set to 0.25 V vs OC, and the scan rate was set to 0.1666 mV / s;
[0075] (9) The above tests were repeated and the average values of open circuit potential, electrochemical impedance, corrosion current and corrosion potential were read and calculated to ensure the reliability of the data.
[0076] Electrochemical corrosion tests were carried out on the Ti-6Al-4V alloy samples treated with direct current pulses in Example 1-2 and the initial state samples in Comparative Example 1 in a 0.9wt.% NaCl electrolyte environment at a constant temperature of 37°C. The curves of the open circuit potential change with time are shown in FIG. Figure 1 The Tafel polarization curves obtained by conducting Tafel polarization tests on the Ti-6Al-4V alloy samples treated with direct current pulses in Example 1-2 and the initial state samples in Comparative Example 1 in a 0.9wt.% NaCl electrolyte at 37°C are shown in Figure 2. Figure 2 The corrosion potential and corrosion current average values of different samples were calculated. The electrochemical impedance spectroscopy analysis curves of the Ti-6Al-4V alloy samples treated with direct current pulses in Example 1-2 and the initial state samples in Comparative Example 1 were obtained in a 0.9wt.% NaCl electrolyte environment at a constant temperature of 37°C. Figure 3 shown.
[0077] Figure 1 The curves of open circuit potential change over time of the Ti-6Al-4V alloy samples treated with direct current pulses in Examples 1 and 2 and the initial state sample of Comparative Example 1 (Comparative Example 1) in 0.9 wt.% NaCl solution. Figure 1 It can be seen that after the initial state sample enters the electrolyte, the potential moves in the positive direction, indicating that a protective passivation film is formed on the surface of the working electrode. As the test time increases, the open circuit potential continues to increase. In the final stage of the test, the open circuit voltage stabilizes at 0.21V and maintains this value until the end of the test. 140A / mm 2 -65ms (Example 1) The initial potential of the sample is almost the same as that of Comparative Example 1. After that, its open circuit potential shows a trend of continuous increase. When the sample is immersed for 40000s, it reads 140A / mm 2 - The open circuit voltage of the 65ms sample is 0.25V. In addition, 140A / mm 2 -70ms (Example 2) The initial potential (0.17V) of the sample is significantly higher than that of Comparative Example 1 and Example 1. As the test continues, near the middle of the test time, the open circuit voltage drops from 0.33V to 0.29V. Subsequently, the test open circuit potential increases again, and the highest open circuit potential is read as 0.34V. The potential fluctuation phenomenon is observed on the open circuit potential curve of Example 2, which indicates that there is a growth and dissolution process of the passivation film on the surface of the sample at the same time, and the passivation film product is not yet stable at this time. During the entire test process, the open circuit potential of Example 2 is significantly higher than that of Example 1 and Comparative Example 1, indicating that when the DC pulse density is 140A / mm2 When the electric pulse duration is 70 ms, the open circuit potential of the Ti-6Al-4V alloy is significantly improved, and the improvement is 61.9% compared with Comparative Example 1.
[0078] Figure 2 The Tafel polarization curves of Ti-6Al-4V alloy in 0.9wt.% NaCl solution at 37°C are shown in Comparative Example 1, Example 1, and Example 2. Figure 2 The vertical axis is the logarithm of the current density. The cathode and anode branches of the Tafel curve are used to determine the corrosion current (Icorr) and corrosion potential (Ecorr) of the Ti-6Al-4V alloy material. Generally, the higher the corrosion potential Ecorr of the material, the lower the corrosion current Icorr, which means the better the corrosion resistance of the material. Figure 2 As shown in Figure 2, the corrosion potential of the initial sample is 143.70mV and the corrosion current is 1021.91pA. When the current density of the DC pulse treatment is 140A / mm 2 When the electric pulse duration was further extended to 70ms, the corrosion potential of the sample increased to 210.73mV and the corrosion current decreased to 2.79pA, indicating that the electrochemical corrosion performance of the Ti-6Al-4V alloy sample was significantly improved by direct current pulse treatment.
[0079] Figure 3 The electrochemical impedance spectra of the Ti-6Al-4V alloy in comparative example 1, example 1, and example 2 in 0.9wt.% NaCl solution at 37°C are shown in FIG. Figure 3 The horizontal and vertical coordinates represent the real and imaginary parts of the impedance capacitance arc radius, respectively. By applying small-amplitude sinusoidal interference signals of different frequencies to the system, the equivalent circuit in the electrochemical corrosion process is inferred to achieve the purpose of obtaining the electrode interface structure and kinetic information. For Example 1, Example 2 and Comparative Example 1, capacitance arc curves of different radii are observed in the Nyquist diagrams of the three groups of samples. The larger the radius of the capacitance arc, the higher the impedance value of the passivation film. Compared with the initial state sample, as the electric pulse duration increases from 65ms to 70ms, the capacitance arc radius increases significantly, which indicates that 140A / mm 2 -70ms The passivation film formed on the surface of the sample has better corrosion resistance.
[0080] It can be seen from the above examples and comparative examples that the open circuit potential, corrosion potential and electrochemical impedance value of the commercial hot-processed Ti-6Al-4V alloy treated with direct current pulses provided by the present invention have all been significantly improved. 2When the electric pulse duration was extended from 65ms to 70ms, the open circuit potential and corrosion potential of the sample were further increased by 61.9% and 35.6%, respectively.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a Ti-6Al-4V alloy resistant to electrochemical corrosion using a direct current pulse, characterized in that: The following steps are involved: Step S1, firstly, wire cutting is performed on the Ti-6Al-4V alloy raw material to obtain a plurality of electrochemical corrosion samples; Step S2, mechanically grinding, ultrasonically cleaning and constant temperature drying the electrochemically corroded sample obtained in step S1 in sequence to obtain an initial alloy sample for direct current pulse treatment; Step S3, then placing the initial alloy sample of step S2 on the test bench, and connecting two ends of the initial alloy sample to two copper plate electrodes in the power supply system respectively; Step S4, starting the power supply, subjecting the initial alloy sample to direct current pulse treatment, and subjecting the initial alloy sample after direct current pulse treatment to mechanical grinding, ultrasonic cleaning and constant temperature drying in sequence, and finally obtaining an electrochemical corrosion resistant Ti-6Al-4V alloy.
2. The method for preparing a Ti-6Al-4V alloy resistant to electrochemical corrosion using a direct current pulse according to claim 1, characterized in that: In the step S3, a conductive copper block is arranged between the copper plate electrode and the end of the initial alloy sample, and the conductive copper block is used to conduct electricity to the initial alloy sample.
3. The method for preparing a Ti-6Al-4V alloy resistant to electrochemical corrosion using a direct current pulse according to claim 1, characterized in that: In step S4, the specific method of performing direct current pulse treatment on the initial alloy sample is: starting the power supply and inputting an instantaneous direct current pulse of a specific current density into the initial alloy sample.
4. The method for preparing a Ti-6Al-4V alloy resistant to electrochemical corrosion using a direct current pulse according to claim 1, characterized in that: In step S4, the current density of the instantaneous DC pulse is 130A / mm 2 ~150A / mm 2 .
5. The method for preparing a Ti-6Al-4V alloy resistant to electrochemical corrosion using a direct current pulse according to claim 1, characterized in that: In the step S4, the DC pulse processing time of the instantaneous DC pulse is 35 ms to 80 ms.
6. The method for preparing a Ti-6Al-4V alloy resistant to electrochemical corrosion using a direct current pulse according to claim 1, characterized in that: In step S4, the current density of the instantaneous DC pulse is 140A / mm 2 , the DC pulse processing time of the instantaneous DC pulse is 70ms.
7. The method for preparing a Ti-6Al-4V alloy resistant to electrochemical corrosion using a direct current pulse according to claim 1, characterized in that: In step S4, the application rate of the instantaneous direct current pulse is greater than 11.4 K / ms.
8. The method for preparing a Ti-6Al-4V alloy resistant to electrochemical corrosion using a direct current pulse according to claim 1, characterized in that: An induction coil device is installed at the input cable of the power supply, and the induction coil device is used to measure the current released by the power supply; a thermistor infrared thermometer is set at the center position of the initial alloy sample, and the thermistor infrared thermometer is used to measure the temperature rise of the initial alloy sample during the direct current pulse treatment process.
9. The method for preparing a Ti-6Al-4V alloy resistant to electrochemical corrosion using a direct current pulse according to claim 1, characterized in that: In the step S1, the chemical composition of the Ti-6Al-4V alloy raw material mainly includes: Ti, Al, V, Fe, C, and N; the mass percentage content of the aluminum Al element is 5.5% to 6.8%, the mass percentage content of the vanadium V element is 3.5% to 4.5%, the mass percentage content of the iron Fe element is 0.3% to 0.4%, the mass percentage content of the carbon C element is 0.1% to 0.2%, and the mass percentage content of the nitrogen N element is 0.05% to 0.1%.
10. A Ti-6Al-4V alloy resistant to electrochemical corrosion using direct current pulses, characterized in that: The electrochemical corrosion resistant Ti-6Al-4V alloy is prepared by the preparation method as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Cast titanium alloy for oral restoration
CN101831575A
Preparation of antifouling ceramic membrane electrolyte for titanium alloy surface and micro-arc oxidation method
CN103233260A
Method for calibrating titanium alloy Ti-6Al-4V test
CN105572316A
Electric pulse treatment method for improving defect or structure state of selective laser melting additive manufacturing titanium alloy
CN113215508A
Super-wetting material as well as preparation method and application thereof
CN114459881A